2022
DOI: 10.1088/1361-648x/ac5e06
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependent band structure of α-bismuthene grown on epitaxial graphene

Abstract: Along with the great interest in two-dimensional elemental materials that has emerged in recent years, atomically thin layers of bismuth have attracted attention due to physical properties on account of a strong spin-orbit coupling. Thickness dependent electronic band structure must be explored over the whole Brillouin zone in order to further explore their topological electronic properties. The anisotropic band structures along zig-zag and armchair directions of α-bismuthine (α-Bi) were resolved using the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…the shorter axis in real space, which corresponds to the zig-zag direction of Bi(110) (see also the inset of figure 2(c)), is aligned approximately with the armchair direction of graphene. However, it is misaligned by ±(1.75 ± 0.5) • , resulting in two sub-domains, as already observed by Takahashi et al [15], and indicated by solid and dotted lines in figure 1(a). For reference, figure 1(b) shows the LEED image for a Bi coverage of 0.15 BL, where the Bi spots are barely visible, i.e.…”
Section: Bi(110) Majority Islands Elongated In the Graphene Armchair ...supporting
confidence: 66%
See 4 more Smart Citations
“…the shorter axis in real space, which corresponds to the zig-zag direction of Bi(110) (see also the inset of figure 2(c)), is aligned approximately with the armchair direction of graphene. However, it is misaligned by ±(1.75 ± 0.5) • , resulting in two sub-domains, as already observed by Takahashi et al [15], and indicated by solid and dotted lines in figure 1(a). For reference, figure 1(b) shows the LEED image for a Bi coverage of 0.15 BL, where the Bi spots are barely visible, i.e.…”
Section: Bi(110) Majority Islands Elongated In the Graphene Armchair ...supporting
confidence: 66%
“…The amount was controlled by a quartz crystal microbalance. The thickness calibration was done by observing the conductance oscillations during the deposition of Bi on a Bi(111) film on Si(111) at a substrate temperature of 12 K, and then converting the result from Bi(111) bilayers (1BL = 1.14 × 10 15 atoms cm −2 ) to Bi(110) bilayers (1BL = 1.85 × 10 15 atoms cm −2 [15]). The Bi layers were investigated as deposited and after an annealing step at 410 K for 30 min.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations